Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation. Issue 2 (4th May 2018) - Mutu, Margaret
ABSTRACT: Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country's founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments' true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.